2010
DOI: 10.1016/j.physbeh.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Circular swimming in mice after exposure to a high magnetic field

Abstract: There is increasing evidence that exposure to high magnetic fields of 4 tesla and above perturbs the vestibular system of rodents and humans. Performance in a swim test is a sensitive test of vestibular function. In order to determine the effect of magnet field exposure on swimming in mice, mice were exposed for 30-min within a 14.1 tesla superconducting magnet and then tested at different times after exposure in a 2-min swim test. As previously observed in open field tests, mice swam in tight counter-clockwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Therefore, the absence of circling in the rats removed slowly from the magnet could be accounted for entirely by the additional restraint time prior to recording their post-exposure locomotor activity. This is consistent with our previous observations that magnet-induced circling decays away within 2–3 minutes after magnet exposure [15]. (Rearing, however, was suppressed in both groups, which is consistent with the prior observation that suppression of rearing persists for ~10 min after exposure [16].…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the absence of circling in the rats removed slowly from the magnet could be accounted for entirely by the additional restraint time prior to recording their post-exposure locomotor activity. This is consistent with our previous observations that magnet-induced circling decays away within 2–3 minutes after magnet exposure [15]. (Rearing, however, was suppressed in both groups, which is consistent with the prior observation that suppression of rearing persists for ~10 min after exposure [16].…”
Section: Resultssupporting
confidence: 92%
“…In rodents, we have found that exposure to static magnetic fields of 7 T or greater induced circular locomotion (15,16), conditioned taste aversion (CTA) (16), and c-Fos induction in the vestibular nuclei of the brain stem (28). These effects are consistent with vestibular perturbation induced by more conventional stimuli such as whole-body rotation.…”
mentioning
confidence: 53%
“…The circling is observed when animals walk in a test chamber but is more pronounced when activity is elicited by swimming. The circling and other postural deficits persist for less than 10 min after removal from the magnet (15). In this study, the induction of circular swimming varied with the angle of exposure, with a graded response from maximum at 0°to a minimum at 90°, back to maximal response at 180°.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations